Efektivitas Pelaksanaan Pemungutan Pajak Kendaraan Bermotor di Kantor Bersama SAMSAT Sibolga - Arifianti, Sari Maharani; Imsar (Ikatan Da'i Indonesia, 2024)
In general, this study aims to find out the effectiveness of motor vehicle tax collection in offices with Sibolga samsat. This study uses qualitatif descriptive research, which is to find out the value of independent variables, either one or more variables (independent) without making comparisons, or connecting with other variables. As far as data collection techniques are concerned are documentation, interviews and observations. The results of the research showed the effectiveness of motor vehicle tax collection in the Joint Office of Samsat Sibolga has been effective in the collection of motor vehicles tax. Although, there are still many obstacles facing the lack of public awareness to pay taxes on time, which leads to a lot of taxpayers waiting. However, in the process of tax payment procedures is good because it does not take a long time in the management of motor vehicle tax payment.